Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/adb.12050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naltrexone on adolescent alcohol cue reactivity and sensitivity: an initial randomized trial

Abstract: Adolescent alcohol use is associated with myriad adverse consequences and contributes to the leading causes of mortality among youth. Despite the magnitude of this public health problem, evidenced-based treatment initiatives for alcohol use disorders in youth remain inadequate. Identifying promising pharmacological approaches may improve treatment options. Naltrexone is an opiate receptor antagonist that is efficacious for reducing drinking in adults by attenuating craving and the rewarding effects of alcohol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 47 publications
7
81
1
Order By: Relevance
“…Thus, a modest effect on laboratory SA is consistent with what is known about naltrexone's effects on self‐reported drinking quantity during longer periods of treatment. Importantly, the current findings confirm that naltrexone reduces consumption using data collected at the event level—an observation also reported in the context of ecological momentary assessment (EMA) research (Miranda et al , 2014). Moreover, in contrast to RCT and EMA studies—which rely on self‐reports subject to recall and/or reporting biases—this analysis confirms a significant overall medication effect on objective indicators of consumption.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, a modest effect on laboratory SA is consistent with what is known about naltrexone's effects on self‐reported drinking quantity during longer periods of treatment. Importantly, the current findings confirm that naltrexone reduces consumption using data collected at the event level—an observation also reported in the context of ecological momentary assessment (EMA) research (Miranda et al , 2014). Moreover, in contrast to RCT and EMA studies—which rely on self‐reports subject to recall and/or reporting biases—this analysis confirms a significant overall medication effect on objective indicators of consumption.…”
Section: Discussionsupporting
confidence: 88%
“…These investigations confirmed the anti-craving effect of nicotine patches (Bolt et al, 2012;Ferguson et al, 2006;Shiffman et al, 2000Shiffman and Ferguson, 2008), nicotine gum (O'Connell et al, 2007), bupropion Piper et al, 2008), naltrexone (Miranda et al, 2013;Tidey et al, 2008), varenicline (Gass et al, 2012), but also individualized cognitive-behavioral treatment (IATP) compared to traditional cognitive-behavioral treatment (CBT) (Litt et al, 2009). Heroin craving was found to be higher in patients with higher doses of methadone (De Vos et al, 1996).…”
Section: Intra-individual Variablesmentioning
confidence: 54%
“…Several other EMA studies also examined the impact of cues on craving, and reported greater craving in the presence of substancerelated cues (Gass et al, 2012;Miranda et al, 2013;Warthen and Tiffany, 2009;Wray et al, 2011), such as seeing the substance or seeing other people using substances Gwaltney et al, 2005;Kennedy et al, 2013;McCarthy et al, 2006;O'Connell et al, 2011;Piasecki et al, 2008). Other studies confirmed the protective effect of self-efficacy (Gwaltney et al, , 2005Shiyko et al, 2012;Van Zundert et al, 2011) and the use of coping strategies (Brodbeck et al, 2013;O'Connell et al, 2007) on craving.…”
Section: Intra-individual Variablesmentioning
confidence: 88%
“…In order to provide an efficient blockade of opioid receptors, the present study used naltrexone, a clinically relevant opioid receptor antagonist with greatest affinity for the μ-and κ-opioid receptors in humans (Emmerson et al, 1994;Toll et al, 1998). The efficacy of naltrexone for substance use disorders (eg, Miranda et al, 2014;Monti et al, 1999;Ray et al, 2008;Syed and Keating, 2013), including amphetamine (Itzhak and Ali, 2002;Jayaram-Lindstrom et al, 2008) and methamphetamine (Anggadiredja et al, 2004;Ray et al, 2015a) may be subserved by its attenuation of drug craving. Naltrexone is thought to modulate reinforcementdriven behavior via blocking dopamine release in the mesolimbic dopamine system, primarily acting on the pathway from the ventral tegmental area (VTA) to the ventral striatum (ie, nucleus accumbens (NAcc)) (Benjamin et al, 1993;Lee et al, 2005); however, this theoretical pathway of naltrexone's effects on behavior has not been directly tested in human models of cue-induced craving.…”
Section: Introductionmentioning
confidence: 99%